Retirement and Continuation of Employment Relations: Annotation of Supreme Court Circular Letter Number 5 of 2021 - Willy Farianto (Lex Publica, 2022)
Retirement is a time when a worker stops working because he is old or has entered old age. At that time, laws and regulations stipulated that termination of employment could be carried out for the reason that workers were entering retirement age. However, sometimes it is common to find a company still employing retirees, whether they are employees who have retired but are still employed or have had their term of office extended, or who have retired and then been called back to work. For employees who have retired and are re-employed, the company can use a Specific Time Work Agreement (Perjanjian Kerja Waktu Tertentu /PKWT) by taking into account the time period and completion of work as stipulated in Article 4 paragraph (1) amended by Article 5 paragraphs (1) and (2) and amended by Article 6 of Government Regulation No. 35 of 2021. In line with the absence of laws and regulations prohibiting employers or companies from re-employing workers who have reached retirement age, the Supreme Court issued a Supreme Court Circular (Surat Edaran Mahkamah Agung/SEMA) Number 5 of 2021 concerning Enforcement of the Formulation of the Results of the 2021 Supreme Court Chamber Plenary Meeting as a Guideline for the Implementation of Duties for the Court in which it regulates the rights of workers who retire and then are reemployed.